Hide and Die Syndrome: Autopsy Detection of a Rare Case of Paradoxical Undressing & Terminal Burrowing (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Hypothermia is a condition in which core temperature of the body drops below that required for normal metabolism and body functions, which is defined as 35°C (95°F). “Hide and Die Syn drome” or “Terminal Burrowing” is a strange condition seen in fatal hypothermia, particularly in old persons. Long exposure to the severe cold produces paralysis of the thermo-regulatory mechanism, which leads to the aberrant feeling of a higher body temperature and the victim may take off some or all of his clothing known as ‘Paradoxical Undressing’. In the final stage of hy pothermia, the brain stem produces a burrowing-like behavior in which the person hides himself in a strange and enclosed space. Subsequently his dead body may be found there itself, which could be either naked or partly dressed. In such cases, the scene of crime usually produces a great confusion and suggests the investigators that the deceased might have attempted conceal ment before coma and death, which is known as ‘Hide and Die Syndrome’. Such a rare case was brought to us for the autopsy examination in which completely naked body of an old age person was recovered from a partially enclosed tank in the vicinity of a non-functional railway station at Rajkot City of Gujarat. The investigating officers were suspicious of murder with pos sibility of sexual assault as well, but after meticulous autopsy examination and all other necessary investigations it was concluded as a case of Hide & Die Syndrome. This article is presented here with an aim to highlight the medico legal aspect of rare variety of death from exposure to extreme environmental temperature in India.
Keywords: Hypothermia; Paradoxical Undressing and Hide and Die Syndrome